2020
DOI: 10.37936/ecti-eec.2020181.218580
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Performance of Suction Head in a Cleaning Process of Hard Disk Drive Factory

Abstract: The suction head is a component positioned at the vacuum cleaner's tip and used to control airflow to eliminate small particles, thus preventing contamination from occurring during the cleaning process at a hard disk drive (HDD) manufacturing factory. At the factory, 2 suction head types (bowl and straight) were used in the cleaning process. From an actual usage, the operators questioned the operating condition's performance and suitability. In order to seek an answer to the questions, the researchers used com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
(16 reference statements)
2
9
0
Order By: Relevance
“…The proposed SHs were investigated for their cleaning performance in two usage situations: in space and 5 mm above the work area. The 5 mm is the optimal distance for cleaning mentioned in [11,12]. This section describes the detail step-by-step from the start until the suitable SH shape was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The proposed SHs were investigated for their cleaning performance in two usage situations: in space and 5 mm above the work area. The 5 mm is the optimal distance for cleaning mentioned in [11,12]. This section describes the detail step-by-step from the start until the suitable SH shape was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…From the calculation based on the actual conditions at the factory, we found that the Reynolds numbers (Re) were between 5 × 10 3 -2 × 10 5 , which matched the SST k-ω turbulence model. The SST k-ω equations can be written as [6][7][8]12,25,27]:…”
Section: Sst K-ωmentioning
confidence: 99%
See 3 more Smart Citations